Gender Disparities in Utilizing Language Features on YouTube Vlogs - Rafi'atussyifa, Gusti; Nor, Hidayah (Pusat Studi Gender dan Anak Universitas Islam Negeri Antasari Banjarmasin, 2023)
This study delves into gender-specific linguistic variations in YouTube vlogs, analysing language features employed by 30 daily English language video vlogs, evenly split between 15 male and 15 female vloggers. Employing a qualitative research design with content analysis, the study identifies prevalent language features and scrutinizes their typologies and intended functions through a systematic four-step method, encompassing data segmentation, code formulation, category development, and the identification of overarching themes. Taboo and swearing, directive and command language feature prominently among male vloggers. In contrast, female vloggers utilize compliments, hedges, tag questions, and questions to engage with their audience on YouTube. This study offers valuable insights into the distinct language patterns of male and female vloggers, contributing to a nuanced understanding of communication dynamics in online platforms and shedding light on the intersection of gender and language in online contexts.